3D heart morphological changes in response to developmental temperature in zebrafish: More than ventricle roundness. (14th October 2020) - Dimitriadi, Anastasia; Geladakis, George; Koumoundouros, George
Abstract: A new, three‐dimensional geometric morphometric approach was assessed to study the effect of developmental temperature on fish heart shape utilizing geometric morphometrics of three‐dimensional landmarks captured on digitally reconstructed zebrafish hearts. This study reports the first three‐dimensional analysis of the fish heart and demonstrates significant shape modifications occurring after three developmental temperature treatments ( T D = 24, 28 or 32°C) at two distinct developmental stages (juvenile and adult fish). Elevation of T D induced ventricle roundness in juveniles, males and females. Furthermore, significant differences that have not been described so far in heart morphometric indices (i.e., ventricle sphericity, bulbus arteriosus elongation and relative location, heart asymmetry) were identified. Sex proved to be a significant regulating factor of heart shape plasticity in response to T D . This methodology offers unique benefits by providing a more precise representation of heart shape changes in response to developmental temperature that are otherwise not discernable with the previously described two‐dimensional methods. Our work provides the first evidence of three‐dimensional shape alterations of the zebrafish heart adding to the emerging rationale of temperature‐driven plastic responses of global warming and seasonal temperature disturbances in wild fish populations and in other ectothermic vertebrates as well (amphibians and reptiles). Abstract : We examined the effect of developmental temperature on the three‐dimensional heart shape of zebrafish. We found that temperature experienced during the embryonic and larval stages permanently alters ventricle sphericity and other significant heart morphometric indices in juvenile, male and female fish that have not been described so far.